Pengaruh Kualitas Layanan Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Bus Trans Mebidang - Nur Hazizah; Suhairi; Sri Ramadhani (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2025)
This study examines the relationship between service quality, customer satisfaction, and customer loyalty in the context of Trans Mebidang public transportation, which serves Medan City, Binjai City, and Deli Serdang Regency. Using quantitative methods, data were collected through questionnaires from 399 users and analyzed using SEM with Smart PLS 4.1. The results highlight that service quality significantly influences customer satisfaction, which in turn positively affects customer loyalty. Furthermore, customer satisfaction acts as a mediator between service quality and loyalty, showing that higher satisfaction can enhance user loyalty. These findings emphasize the crucial role of service quality in shaping customer experiences and long-term engagement with public transport services. The study provides valuable insights for transportation service providers to prioritize service improvements and develop sustainable strategies aimed at increasing customer satisfaction and loyalty. Strengthening service quality is key to building a more reliable and user-focused public transportation system.